Faktor-faktor yang mampengaruhi Loyalitas Karyawan: Iklim Organisasi, Kepemimpinan, Kompensasi - Avivah Shafa Nada; Cris Kuntadi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
In scientific studies or publications, previous or related research is of greatest importance. Previous studies and related research support the theory and phenomenon of the relationship or impact between variables. This lecture discusses the study of organizational behavior and how employee loyalty affects company atmosphere, leadership, and pay. The purpose of this literature is to establish a hypothesis about how related factors interact with each other, which can be used in future studies. Employee loyalty is influenced by company atmosphere, leadership and pay, a document analysis found.